The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1002/cne.902770110
|View full text |Cite
|
Sign up to set email alerts
|

Development of neurons in the ectostriatum of normal and monocularly deprived zebra finches: A quantitative Golgi study

Abstract: The postnatal development of the main neuron type in the ectostriatum, the telencephalic station of the tectofugal pathway, was followed in normally reared and monocularly deprived zebra finches by using the Golgi method. Three parameters were investigated: dendritic field radius, branching index, and spine density. The results show that all three exhibit the same developmental trend-namely, an increase from day 5 until day 20, followed by a subsequent reduction until adulthood ( > 100 days). Monocular depriva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 91 publications
1
5
0
Order By: Relevance
“…Thus, the effects of monocular deprivation are not confined to the deprived brain side but affect both hemispheres. Such a bilateral deprivation effect has also been shown in zebra finches in which closure of one eye changes tectofugal cell sizes in both brain halves [14,15]. Besides, these results demonstrate that the TTX treatment did not perturb mechanisms of visual discrimination which might have been responsible for asymmetric performances.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Thus, the effects of monocular deprivation are not confined to the deprived brain side but affect both hemispheres. Such a bilateral deprivation effect has also been shown in zebra finches in which closure of one eye changes tectofugal cell sizes in both brain halves [14,15]. Besides, these results demonstrate that the TTX treatment did not perturb mechanisms of visual discrimination which might have been responsible for asymmetric performances.…”
Section: Discussionsupporting
confidence: 51%
“…Right eye deprivation leads to a reversal of the functional and morphological asymmetry pattern, while left-eye deprivation increases right-eye superiority [7,13]. Since it is known that monocular deprivation affects neuronal cell size in the tectofugal pathway [7,[13][14][15] and since anatomical asymmetries are present within this system, the unbalanced visual stimulation can directly influence the differentiation of the tectofugal pathway. The development of this pathway is well known to be controlled by afferent activity [16] and neurotrophic factors are key mediators of this regulation [17].…”
Section: Introductionmentioning
confidence: 98%
“…One hundred/~m coronal vibratome sections were made after processing the brains according to a modification of the Bubenaite Golgi method [22]. Because MNH and ANC can be defined exactly only in 2-DG images, we used other structures, which could be seen in 2-DG as well as in Golgi preparations, as landmarks.…”
Section: Methodsmentioning
confidence: 99%
“…For the measurements, only those of the terminal sections of a dendrite were selected, which were parallel to the surface of the slide. Terminal sections were chosen because earlier studies have shown that these are most strongly affected by experience [41,22,27,33]. The selected sections (20 for each bird) were marked during drawing and the number of spines/ 10 #m estimated with help of a graphics tablet.…”
Section: Methodsmentioning
confidence: 99%
“…1), the birds were deeply anesthetized and perfused with 0.9% NaC1 followed by 10% formaldehyde. After processing the brains according to a modification of the Bubenaite Golgi method [10], 100-~tm transverse vibratome sections were made. In all brain areas, a neuron type characterized by a soma diameter of about 5-10 ~tm and 4-6 radially ordered dendrites with relatively few dendritic spines could be identified.…”
Section: Golgi Experimentsmentioning
confidence: 99%